Occupational health risk of working in garages: comparative study on blood pressure and hematological parameters between garage workers and Haramaya University community, Harar, eastern Ethiopia - Ataro Z; Geremew A; Urgessa F (Dove Medical Press, 2018)
Zerihun Ataro,1 Abraham Geremew,2 Fekadu Urgessa3 1Department of Medical Laboratory Sciences, 2Department of Environmental Health Sciences, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia, 3School of Medical Laboratory Science, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia Background: Occupational exposure to chemicals in garages causes a wide range of biological effects, depending upon the level and duration of exposure. In Ethiopia, there have been few studies conducted to assess the exposure of garage workers to chemicals. Preceding studies have not explored the effect of working in garage on blood pressure and hematological parameters. Therefore, this study aimed to assess differences in blood pressure and hematological parameters among garage workers compared to the Haramaya University community, Harar, eastern Ethiopia.Materials and methods: A comparative cross-sectional study was conducted in Harar town, eastern Ethiopia. Thirty garage workers were selected and compared with 30 age- and sex-matched controls comprising of teachers and students. Demographic and occupational data were collected by using a structured questionnaire by a trained data collector. Blood pressure was measured using sphygmomanometry. Hematological parameters were measured with an automated hematology analyzer. Data were analyzed using Stata version 13.Results: The majority of the garage workers did not implement effective preventive or control measures for workplace chemical exposure. Statistically significant increases were found in systolic (128.67±18.14 vs 106.33 ±9.27 mmHg, P<0.0001), diastolic blood pressure (90.33±11.29 vs 75.67 ±5.68 mmHg, P<0.0001), total white blood cells (7.9±1.51 vs 6.72±2.04×109 cells/L, P=0.0138), and platelets (323.20±48.82 vs 244.1±47.3×109 cells/L, P<0.0001) in garage workers compared to the control group. On the other hand, statistically significant decreases were found in red blood cells (5.13±0.38 vs 5.46±0.36×1012 cells/L, P=0.0006), hemoglobin (14.89±0.71 vs 15.45±0.87 g/dL, P=0.0062), hematocrit (43.98%±1.99% vs 46.4%3±2.32%, P<0.0001), and mean corpuscular volume (83.19±2.93 vs 85.11±3.87 fL, P=0.0353) among garage workers compared to the control group.Conclusion: There were significant differences in blood pressure and hematological parameters between garage workers and the control group. Therefore, appropriate and effective safety measures need to be taken by the workers to prevent possible chemical exposure during routine tasks. Keywords: garage workers, blood pressure, hematological parameters, Harar, Ethiopia